Evidence-Based Medicine: A Graded Approach to Lower Lid Blepharoplasty. Issue 1 (January 2017) - Hashem, Ahmed M.; Couto, Rafael A.; Waltzman, Joshua T.; Drake, Richard L.; Zins, James E.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Define the anatomy of the lower eyelid tarsoligamentous framework and the related periorbital retaining ligaments, and cite their surgical relevance. 2. Perform a systematic functional and aesthetic evaluation of the lower eyelid focusing on the lid-cheek junction, and clinical tests that predict the need for lateral canthal tightening. 3. Enumerate the different approaches to lower eyelid rejuvenation and discuss their merits/limitations. 4. Describe surgical strategies to blend the lid-cheek junction and tighten the lateral canthal retinaculum. Summary: Modern lower lid blepharoplasty requires a thorough understanding of periorbital anatomy, age-related changes of the lid-cheek junction, and the variables controlling lower lid tone and position. The surgical strategies are best used in a graded fashion. The patient with isolated lower lid bags may be treated by transconjunctival fat resection alone. Additional mild skin laxity can be improved with skin pinch or skin-only undermining. Skin resurfacing using chemical peeling or laser can further address fine lines. In these patients with an abnormality of the lid-cheek junction, release of the medial orbicularis oculi muscle and variable amounts of the orbicularis retaining ligament is essential. This is combined with orbital fat resection or repositioning through a transconjunctival or transcutaneous skin-muscle flap. The transcutaneous approach most often necessitates lateral canthal tightening to optimize lid margin control. Generally, the degree of laxity dictates whether a canthopexy or a canthoplasty is most appropriate. Lateral canthal procedures can be applied to patients displaying clinical signs predictive of lid malposition and to those presenting with varying degrees of established lid descent. Abstract : Supplemental Digital Content is available in the text.